COVID-19 pandemic on maternal and child healthcare services and the inclusion of Perinatal Social Workers in effective healthcare delivery in Nigeria - Blessing Ramsey-Soroghaye; Sotonye Gobo; Precious Anyaegbu (Institute of Computer Science (IOCS), 2022)
Women's well-being determines the health of the next generation. Globally, 6,000 children under five die daily and an additional 950 Nigerian children die daily from preventable diseases. These diseases lead to deaths and complications. Social workers as change agents work as perinatal workers in other to help in alleviating most health challenges faced by women and children. Perinatal social workers act as helpers to individuals, families, and communities to enable them to respond to the various psychosocial issues that tend to emerge during the period from pre-pregnancy through an infant’s first year of life. The study utilized a secondary method of data collection and the data was analyzed and discussed. This study recommends that social workers in perinatal health care should be actively involved and included in daily maternal and child health care activities to improve their care and well-being to promote health and prevent diseases. The Nigerian government needs to reinforce their commitments to achieving immunity for its citizens especially women and children by stepping up safe and effective vaccine procurement efforts.